Traditional and Complementary Medicine 2019
DOI: 10.5772/intechopen.82636
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Natural Antioxidants

Abstract: Free radicals and related species have attracted a great deal of attention in recent years. Oxidative stress has been considered a major contributory factor to the diseases. They are mainly derived from oxygen (reactive oxygen species (ROS)) and nitrogen (reactive nitrogen species (RNS)) and are generated in our body by various endogenous systems and exposure to different physicochemical conditions or pathophysiological states. Free radical damage to protein can result in loss of enzyme activity. There are epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2031
2031

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 83 publications
(59 reference statements)
0
24
0
Order By: Relevance
“…This significant activity of MIT could be ascribed to the presence of polyphenolics like tyrosol, umbelliferone, salvianolic, rosmarinic, and corosolic acids in addition to the presence of apigenin glucuronide, acacetin-7- O -rutinoside and other flavonoids which have various therapeutic properties. It has been reported that flavonoids and other polyphenols have vital activities for human health like anticancer, antioxidant, anti-inflammatory effects in addition to their therapeutic actions in managing several obesity complications ( Sekhon-Loodu and Rupasinghe, 2019 , Rasheed and Azeez, 2019 , Stohs et al, 2012 , Di Benedetto et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…This significant activity of MIT could be ascribed to the presence of polyphenolics like tyrosol, umbelliferone, salvianolic, rosmarinic, and corosolic acids in addition to the presence of apigenin glucuronide, acacetin-7- O -rutinoside and other flavonoids which have various therapeutic properties. It has been reported that flavonoids and other polyphenols have vital activities for human health like anticancer, antioxidant, anti-inflammatory effects in addition to their therapeutic actions in managing several obesity complications ( Sekhon-Loodu and Rupasinghe, 2019 , Rasheed and Azeez, 2019 , Stohs et al, 2012 , Di Benedetto et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Natural sources of antioxidants include vegetables, fruits, cereals, nuts, poultry meat, ruminant meat, fish, and others. They are classified into several classes depending on whether their source is natural or synthetic, or on their chemical nature, being enzymatic or non-enzymatic, or according to the nature of antioxidant reactions (Rasheed and Azeez, 2019).…”
Section: Classification Of Antioxidantsmentioning
confidence: 99%
“…However, aerobic organisms can synthesize enzymatic (e.g., superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (Gr)) and non-enzymatic (glutathione (GSH), oxidized glutathione (GSSG)) antioxidants that minimize cellular damage. Antioxidants can transfer electrons to these oxidizing agents (ROS) by neutralizing them and reducing chain reactions that can cause cell damage [ 27 ], reaching cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%